An Integrated Hospital Protocol for Persons With Injection-Related Infections May Increase Medications for Opioid Use Disorder Use but Challenges Remain. (2nd September 2020) - Eaton, Ellen F; Lee, Rachael A; Westfall, Andrew O; Mathews, R E; McCleskey, Brandi; Paddock, Cayce S; Lane, Peter S; Cropsey, Karen L
Abstract: Background: Hospital-based strategies that link persons with infectious complications of opioid use disorder (OUD) to medications for OUD (MOUD) are of great interest. The objective of this study is to determine whether a hospital-based protocol would increase the use of MOUD and to identify barriers to MOUD during admission and at the time of discharge. Methods: This study included participants with a documented or suspected history of injection drug usage receiving care for an infection at the University of Alabama at Birmingham Hospital from 2015 to 2018. The protocol, the intravenous antibiotic and addiction team (IVAT), included Addiction Medicine and Infectious Diseases consultation and a 9-item risk assessment. We quantified MOUD use before and after IVAT and used logistic regression to determine factors associated with MOUD. We explored barriers to MOUD uptake using chart review. Results: A total of 37 and 98 patients met criteria in the pre- and post-IVAT periods, respectively. With IVAT, the percentage with OUD receiving MOUD significantly increased (29% pre-IVAT and 37% post-IVAT; P = .026) and MOUD use was higher in "high risk" participants (62%). Clinical and sociodemographic factors were not associated with MOUD receipt. Conclusions: A hospital-based protocol may increase the use of MOUD; however, the uptake of MOUD remains suboptimal (<50%).